Analisis Persebaran Emisi Gas Sulfur Dioksida dari Unit 2 Pabrik Sulphuric Acid PT Petrokimia Gresik Menggunakan Model AERMOD - Muhammad Daffa Shidqi; Naniek Ratni Juliardi A. (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This study investigates SO2 emissions from the Stack 2 sulphuric acid production plant and their impact on human health and the environment. Using AERMOD software, the study maps the SO2 distribution of PT Petrokimia Gresik to provide management data and analyse the relationship between emissions and meteorological factors. The results show a peak SO2 concentration of 7,849 μg/m3, which is below the 24- hour air quality standard of 75 μg/m3. Emissions are mainly north-easterly during the rainy season due to the westerly monsoon. There is a direct proportional relationship between SO2 concentrations and temperature, and an inverse relationship with humidity and wind speed. Positive coefficients for SO2 concentrations and negative coefficients for independent variables in linear regression indicate their effecton emissions when other factors are held constant.